Frequency of subclinical atherosclerosis in Brazilian HIV-infected patients - Salmazo, Péricles Sidnei [UNESP]; Bazan, Silméia Garcia Zanati [UNESP]; Shiraishi, Flávio Gobbis [UNESP]; Bazan, Rodrigo [UNESP]; Okoshi, Katashi [UNESP]; Hueb, João Carlos [UNESP] (Sociedade Brasileira de Cardiologia, 2018)
Background: AIDS as well as atherosclerosis are important public health problems. The longer survival among HIV-infected is associated with increased number of cardiovascular events in this population, and this association is not fully understood. Objectives: To identify the frequency of subclinical atherosclerosis in HIV-infected patients compared to control subjects; to analyze associations between atherosclerosis and clinical and laboratory variables, cardiovascular risk factors, and the Framingham coronary heart disease risk score (FCRS). Methods: Prospective cross-sectional case-control study assessing the presence of subclinical atherosclerosis in 264 HIV-infected patients and 279 controls. Clinical evaluation included ultrasound examination of the carotid arteries, arterial stiffness by pulse wave velocity (PWV) and augmentation index (AIx), laboratory analysis of peripheral blood, and cardiovascular risk according to FCRS criteria. The significance level adopted in the statistical analysis was p < 0.05. Results: Plaques were found in 37% of the HIV group and 4% of controls (p < 0.001). Furthermore, carotid intima-media thickness was higher in the HIV group than in controls (p < 0.001). Patients with carotid plaque had higher fasting glucose, total cholesterol, low-density lipoprotein cholesterol, and triglycerides than those without plaques. The presence of HIV, adjusted for age, overweight/obesity, and smoking increased by almost fivefold the risk of atherosclerotic carotid plaque (OR: 4.9; 95%CI: 2.5-9.9; p < 0.001). Exposure to protease inhibitors did not influence carotid intima-media thickness, was not associated with carotid plaque frequency, and did not alter the mechanical characteristics of the arterial system (PWV and AIx). Conclusions: HIV-infected patients are at increased risk of atherosclerosis in association with classical cardiovascular risk factors. Treatment with protease inhibitors does not promote functional changes in the arteries, and shows no association with increased frequency of atherosclerotic plaques in carotid arteries. The FCRS may be inappropriate for this population.
Frequência de aterosclerose Subclínica em Brasileiros infectados pelo HIV
Keywords: Atherosclerosis/complications; Cardiovascular diseases/mortality; Carotid intima media carotideo; HIV; Risk factors; Vascular stiffness